Role of the cardiac extracellular matrix in the onset and progression of heart failure - N. N. Ilov; K. Sh. Arnaudova; A. A. Nechepurenko; A. L. Yasenyavskaya; O. A. Bashkina; M. A. Samotrueva (Российский кардиологический журнал)
Any cardiovascular disease leads to heart failure (HF) — a complex clinical syndrome, the course of which is probably specified by the influence of cardiovascular factors on cardiac extracellular matrix (ECM).The presented literature data indicate that the cardiac ECM is an important pathophysiological link in the onset and progression of HF. The morphological and electrical remodeling negatively affects the systolic and diastolic functions of the heart. Impaired myocardial blood delivery, cellular maladaptation, atrial and ventricular arrhythmias are additional mechanisms of the influence of myocardial fibrosis on HF course.Understanding this role of ECM and the development of algorithms for verifying the individual status of ECM in cardiovascular patients can provide additional data on the course of HF, help to assess the risk of adverse cardiovascular events and effectively control the ongoing pharmacological and non-drug therapy.